Strategi Pemasaran Kopi pada Perusahaan Kopi Banyuatis - NI LUH ADE DESI SINTIYA DEWI; IGA OKA SURYAWARDANI; I DEWA GEDE RAKA SARJANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2016)
Abstract Marketing Strategy of Banyuatis Coffee Company This research identify internal environment (strengths and weaknesses) and external environment (opportunities and threats), business position and marketing strategy that should be implemented by Banyuatis Coffee Company method of analysis was used based on the company environment that consists of Internal Factor Evaluation, External Factor Evaluation and Boston Consulting Group and swot analysis. The result show that the total score of Internal Factor Evaluation matrix is 2.76. The result show the total score of the External Factor Evaluation matrix is 2.75. Result from Boston Consulting Group matrix analysis swot that the growth rate of Banyuatis Coffe Campany is 23,9% and the value of relative market share in 2013 was 0.70 and in 2014 at 0.67. Position Banyuatis Coffee Company is in cell question mark which shows that the position of relatively low market share but to compete in an industry that is rapidly growing market. Based on the position of the company, can be produced alternative company strategies that should be applied to companies that market penetration strategies, market development and product development. Keywords: marketing strategy, coffee, internal environment, external environment.